Updating the Legal Regulations on Land Acquisition for Public Interest in Achieving a Balance between the Protection of Community Rights and the Acceleration of National Development - Hendro Widodo; Zainal Arifin Hoesein (SULTAN ADAM: Jurnal Hukum dan Sosial, 2026)
This study aims to analyze the legal provisions for land acquisition for public interest in the Indonesian legal system, identify various legal problems that have resulted in the lack of balance between the protection of community rights and the acceleration of national development, and formulate a concept for equitable legal reform as a form of ius constituendum. The study uses a normative juridical method with a statutory and conceptual approach. The results of the study indicate that although land acquisition regulations have been regulated through Law Number 2 of 2012 concerning Land Acquisition for Development in the Public Interest as adjusted through Law Number 6 of 2023 and Government Regulation Number 19 of 2021, in practice, various problems are still found in the form of an imbalance in the bargaining position between the government and the community, limited community participation, compensation disputes, the use of consignment mechanisms that have the potential to reduce the protection of community rights, and suboptimal protection for vulnerable groups. Legal reform is needed through strengthening the principle of meaningful participation, refining compensation mechanisms to cover both physical and non-physical losses, limiting the use of consignment, and harmonizing the public interest and human rights protection to create a land acquisition system that is fair, legally certain, and supports sustainable national development.